DIFFERENT SYSTEMS IN PREPARATION OF SEED-BED AND THEIR EFFECTS ON GROWTH AND YIELD PROPERTIES OF COTTON CROP - Aziz R.Al-Banna (Mesopotamia Journal of Agriculture)
The field study was carried out in 1999 at Salamiyia area on a land in which the soil texture is a mixed clayey one in order to study the effect of the soil preparation on the growth of cotton crop (Ashoor type). The study included four levels represented by four soil preparation systems, these treatments distributed according to the R.C.B.D. design in three replicates for each (first: subsoiler plow in addition to two perpendicular plowing with an inverse disc plow + spring teeth harrowing, second: subsoiler plow in addition to two perpendicular plowing with an moldboard plow + spring teeth harrowing, third: subsoiler plow in addition to two perpendicular plowing with a disc and mold-board plows + spring teeth harrowing, fourth: subsoiler plow in addition to two perpendicular plowing with an chisel plow, in addition to that a control treatment as fifth treatment was executed).The main result of this study was that the first, second and third treatment showed significant effect on most of growth properties of cotton crop. While the first, second and third treatments were equal in their effect on the number of mature bulls, the weight of the first harvesting and mean of weight of one bull, and also showed significant effect on the other studied properties.